An Empirical Analysis of China's Export Behavior - Saxena, Sweta (IMF Working Papers; Working Paper, 2002)
This paper studies the behavior of China's exports from the mid-1980s through 2001. Extensive quarterly data on values and quantities of major export products have been taken from Chinese customs statistics to form a panel data set. The data are used to estimate export supply price elasticities, including by industry groups. The extensive product level data permits the use of panel estimation techniques in order to increase the power of the testing methodology. Aggregate quarterly export unit price indices are also constructed and thereby provide an input to future research on China's trade.